(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines modern methods of developing intellectual potential among youth through the preservation and promotion of national values. It emphasizes the importance of integrating cultural, ethical, and historical values into educational and social programs to enhance critical thinking, creativity, and problem-solving skills. The study highlights innovative pedagogical approaches, interactive learning technologies, and cultural activities that contribute to shaping well-rounded, socially responsible, and intellectually capable individuals. Furthermore, the article discusses the role of national identity and moral upbringing in fostering intellectual growth, as well as strategies for effectively implementing these methods in contemporary educational practices.